Evaluation of ELISA and Microscopy to Diagnose Intestinal Parasitic Infections in Patients of Pediatric Age Group: A Comparative Approach - Chand Nigam; Gopa Banerjee; Prashant Gupta; Vimala Venkatesh; S. K. Verma; Shalini Tripathi (New Frontiers in Medicine and Medical Research Vol. 14, 2021)
Background: Intestinal parasitic Infections (IPI’S) are major health problem in most parts of the world; especially in the under developed and developing countries. Giardia lamblia, Entamoeba histolytica, Ascaris lumbricoides and hookworm are commonly encountered parasites. The study was planned to estimate the proportion of IPI’s in patients of pediatric age group and do a comparative evaluation of ELISA and Microscopy for Giardia. Materials and methods: Stool samples were taken from 200 patients of pediatric age group with the giveninclusion criter ia, during August 2017 to July 2018. Microscopy, formalin ethyl acetate concentration method and ELISA for Giardia was performed. Results: The prevalence of intestinal parasitic infections in our study was found to be 28%. The most common pathogenic parasite was found to be Giardia lamblia (19.5%) followed by Entamoeba histolytica (4.5%). In our study, stool samples positive by Microscopy and formalin ethyl acetate concentration were 8% and 15%. ELISA and Rapid kit test were found to detect higher proportion of Giardia as compared to Formalin ethyl acetate concentration method and Microscopy (Saline and Iodine mount). Conclusion: The prevalence of intestinal parasitic infections in our study was 28%. The most common parasite was Giardia lamblia followed by Entamoeba histolytica. The study showed that parasitic infections were common in patients of uneducated families. Patients who did not wash their hands with soap and water before meals and after using toilet were at increased risk.